Novel magnetic multicore nanoparticles designed for MPI and other biomedical applications: From synthesis to first in vivo studies - Kratz, Harald; Taupitz, Matthias; Ariza de Schellenberger, Angela; Kosch, Olaf; Eberbeck, Dietmar; Wagner, Susanne; Trahms, Lutz; Hamm, Bernd; Schnorr, Jörg (PloS one, 2018)
Synthesis of novel magnetic multicore particles (MCP) in the nano range, involves alkaline precipitation of iron(II) chloride in the presence of atmospheric oxygen. This step yields green rust, which is oxidized to obtain magnetic nanoparticles, which probably consist of a magnetite/maghemite mixed-phase. Final growth and annealing at 90°C in the presence of a large excess of carboxymethyl dextran gives MCP very promising magnetic properties for magnetic particle imaging (MPI), an emerging medical imaging modality, and magnetic resonance imaging (MRI). The magnetic nanoparticles are biocompatible and thus potential candidates for future biomedical applications such as cardiovascular imaging, sentinel lymph node mapping in cancer patients, and stem cell tracking. The new MCP that we introduce here have three times higher magnetic particle spectroscopy performance at lower and middle harmonics and five times higher MPS signal strength at higher harmonics compared with Resovist®. In addition, the new MCP have also an improved in vivo MPI performance compared to Resovist®, and we here report the first in vivo MPI investigation of this new generation of magnetic nanoparticles.